PENYULUHAN KAUM IBU JEMAAT GEREJA KRISTEN INJILI NUSANTARA (GKIN) MENGENAI MAKANAN SEHAT BAGI KELUARGA DI MASA PANDEMI COVID-19 - Manurung, H.; Simanungkalit, F.J.; Naibaho, B. (Buletin Udayana Mengabdi; Vol 23 No 1 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i01.p15, 2023)
The COVID-19 pandemic has made us realize how important it is to maintain a healthy body while increasing the body's immunity. Areas where people whose diets are less diverse have higher suspected cases of Covid-19 compared to those with diverse diets. It is necessary to educate the public regarding the Guidelines for Balanced Nutrition (PGS), the contents of my plate and balanced, nutritious, and diverse (B3) foods to mothers who play the most role in providing food for family members. Community service is carried out at the Gereja Kristen Indonesia Nusantara (GKIN) in Bakaran Batu Village, Lubuk Pakam District, Deli Serdang Regency. The counseling participants were women from the GKIN congregation with a total of 22 people. Counseling aims to increase participants' knowledge about healthy food, and to be able to utilize local food ingredients that are around the neighborhood to improve the nutrition of family food. This method of implementing community service is carried out face-to-face with the activity participants. Healthy food materials were presented to participants and continued with the practice of making pumpkin noodles and carrot meatballs. The Wicoxon test results showed that there was an increase in mothers' understanding of healthy food and being able to make healthy food products, pumpkin noodles and carrot meatballs using local products. The counseling for the women of the Gereja Kristen Indonesia Nusantara (GKIN) Bakaran Batu achieved the target. Keywords: balanced nutrition guidelines, contents of my plate, Covid-19, healthy food, local food